Oncologic Surveillance for Variant Histology Bladder Cancer after Radical Cystectomy. Issue 4 (25th October 2021) - Martini, Alberto; Afferi, Luca; Zamboni, Stefania; Schultz, Julianne G.; Lonati, Chiara; Mattei, Agostino; Karnes, R. Jeffrey; Soligo, Matteo; Stabile, Armando; Di Trapani, Ettore; De Cobelli, Ottavio; Simone, Giuseppe; et al.
Abstract : Purpose: Presently, major guidelines do not provide specific recommendations on oncologic surveillance for patients who harbor variant histology (VH) bladder cancer (BCa) at radical cystectomy. We aimed to create a personalized followup scheme that dynamically weighs other cause mortality (OCM) vs the risk of recurrence for VH BCa, and to compare it with a similar one for pure urothelial carcinoma (pUC). Materials and Methods: Within a multi-institutional registry, 528 and 1, 894 patients with VH BCa and pUC, respectively, were identified. The Weibull regression was used to detect the time points after which the risk of OCM exceeded the risk of recurrence during followup. The risk of OCM over time was stratified based on age and comorbidities, and the risk of recurrence on pathological stage and recurrence site. Results: Individuals with VH had a higher risk of recurrence (recurrence-free survival 30% vs 51% at 10 years, p <0.001) and shorter median time to recurrence (88 vs 123 months, p <0.01) relative to pUC. Among VH, micropapillary variant conferred the greatest risk of recurrence on the abdomen and lungs, and mixed variants carried the greatest risk of metastasizing to bones and other sites compared to pUC. Overall, surveillance should be continued for a longer time for individuals with VH BCa. Notably, patients younger than 60 years with VH and pT0/Ta/T1/N0 at radical cystectomy should continue oncologic surveillance after 10 years vs 6.5 years for pUC individuals. Conclusions: VH BCa is associated with greater recurrence risk than pUC. A followup scheme that is valid for pUC should not be applied to individuals with VH. Herein, we present a personalized approach for surveillance that may allow an improved shared decision.